1997
DOI: 10.1523/jneurosci.17-16-06401.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyrotropin-Releasing Hormone and Its Analogs on Daytime Sleepiness and Cataplexy in Canine Narcolepsy

Abstract: The therapeutic potential of thyrotropin-releasing hormone (TRH) and TRH analogs in narcolepsy, a sleep disorder characterized by abnormal rapid eye movement (REM) sleep and daytime sleepiness, was examined using the canine model. The effects of TRH and the biologically stable TRH analogs CG3703, CG3509, and TA0910 on daytime sleep and cataplexy, a symptom of abnormal REM sleep, were assessed using polysomnographic recordings and the food elicited cataplexy test (FECT), respectively. CG3703 (100 and 400 g/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…Importantly, clinical studies have identified TRH as an anticonvulsant in children with Lennox-Gastaut and West syndromes (Matsumoto et al, 1987;Takeuchi et al, 2001) and in animal models of epilepsy, including absence epilepsy (Ujihara et al, 1991;Momiyama et al, 1996). These likely represent central effects because, as also demonstrated for the sleep-modulating effects (Nishino et al, 1997), TRH doses sufficient to produce anticonvulsive protection do not significantly elevate peripheral thyroid hormone concentrations, and the anticonvulsant actions are not mimicked by activation of the thyroid axis (Nemeroff et al, 1975;Momiyama et al, 1996). TRH is distinct from most commonly used antiepileptic drugs because its actions may involve excitatory rather than inhibitory effects in the CNS (Takeuchi et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Importantly, clinical studies have identified TRH as an anticonvulsant in children with Lennox-Gastaut and West syndromes (Matsumoto et al, 1987;Takeuchi et al, 2001) and in animal models of epilepsy, including absence epilepsy (Ujihara et al, 1991;Momiyama et al, 1996). These likely represent central effects because, as also demonstrated for the sleep-modulating effects (Nishino et al, 1997), TRH doses sufficient to produce anticonvulsive protection do not significantly elevate peripheral thyroid hormone concentrations, and the anticonvulsant actions are not mimicked by activation of the thyroid axis (Nemeroff et al, 1975;Momiyama et al, 1996). TRH is distinct from most commonly used antiepileptic drugs because its actions may involve excitatory rather than inhibitory effects in the CNS (Takeuchi et al, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, intracerebroventricular administration of TRH dramatically reduces sleep time in rats (Hinkle et al, 2002). Furthermore, in canine narcolepsy, TRH analogs alleviate the hallmark symptoms of daytime sleepiness and cataplexy (Nishino et al, 1997). A site of action for these effects has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data suggest that sleep can be modulated by TRH, 126 but the role of TRH in the regulation of sleep in humans has not yet been clarified. Hemmeter et al 127 examined the effects of pulsatile administration of TRH on the sleep EEG pattern and the nocturnal secretions of cortisol and GH in healthy male subjects.…”
Section: Thyrotropin-releasing Hormone (Trh)mentioning
confidence: 99%
“…Clinical and experimental reports demonstrated a role of TRH in the modulation of locomotion, cognition, mood, and sleep. Biologically stable TRH analogues such as CG3703 (montirelin) and TA0910 increase wakefulness and decrease sleep time in narcoleptic canines (Nishino et al, 1997;Riehl et al, 2000). TRH analogues are also known as antiepileptics in animal seizure models (Nillni and Sevarino, 1999) and in clinical use (Kubek and Garg, 2002).…”
Section: Introductionmentioning
confidence: 99%